Research on the Optimization of Information Literacy Education Path for College Students in the Digital Transformation Era - Wang, Lili; Jiang, Xianghui (Journal of Educational Research and Policies, 2025)
Digital transformation and development have put forward new requirements and opportunities for information literacy education for college students. This article sorts out the typical characteristics of information literacy education in colleges and universities, and deeply analyzes the current situation and problems in four aspects of information literacy education for college students: curriculum development, teaching staff, teaching resources, and teaching platforms. Finally, it proposes that colleges and universities should improve the hybrid online and offline course development system, give full play to the subjectivity of the teaching staff, accelerate the construction of a mechanism for the co-construction and sharing of teaching resources, and build a diversified information literacy education platform to further optimize the reform and innovation path of information literacy education for college students.